Leveraging Pseudomonas Stress Response Mechanisms for Industrial Applications - Craig, Kelly; Johnson, Brant R.; Grunden, Amy (Frontiers in Microbiology, 2021)
Members of the genus Pseudomonas are metabolically versatile and capable of adapting to a wide variety of environments. Stress physiology of Pseudomonas strains has been extensively studied because of their biotechnological potential in agriculture as well as their medical importance with regards to pathogenicity and antibiotic resistance. This versatility and scientific relevance led to a substantial amount of information on the stress response of a diverse set of species such as P. chlororaphis, P. putida, P. aeruginosa, and P. syringae. In this review, environmental and industrial stressors including desiccation, heat, and cold stress, are catalogued along with their corresponding mechanisms of survival in Pseudomonas. Mechanisms of survival are grouped by the type of inducing stress with a focus on adaptations such as synthesis of protective substances, biofilm formation, entering a nonculturable state, enlisting chaperones, transcription and translation regulation, and altering membrane composition. The strategies Pseudomonas strains utilize for survival can be leveraged during formulation development of beneficial strains to increase viability and product efficacy.